Analysis of Human Resources Development on Employee Performance at the Bima Regency Transportation Service - Nurul Jumrah; Wulandari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the development of employee performance sources in the Bima Regency transportation service according to human resources. Using purposive sampling, 44 people—all Asn employees—were included in the sample. It can be seen that there is an increase of one unit for each variable based on the findings of the basic linear regression test. Employee performance will be influenced by human resource development by 1,151. The correlation coefficient is 0.675, meaning that the correlation relationship between the independent variable and the dependent variable has a strong correlation relationship. The coefficient of determination value is 45.5%, employee performance (Y) is influenced by human resource development (X). Based on the results of the T test, a calculated value of 5.925 was obtained with a t table value of 2.018, so the hypothesis (Ha) states that the performance of Bima Regency Transportation Service personnel is greatly influenced by human resource development